DIAGNOSTIC STUDY OF EHRLICHIOSIS IN CATTLE OF MOSUL-IRAQ - Basima Abdulfatah Al-Badrani (Basrah Journal of Veterinary Research)
Ehrlichiosis (Ehrlichia spp.) was detected in 132(70 Iranian,32 Turkish and 30 local breed)calves (10-14 months old) and 18 dairy cows of local breed (3-5 years old). Animals were brought to Veterinary Teaching Hospital, College of Veterinary Medicine, University of Mosul –Iraq from different farms of Mosul city-Iraq, with clinical signs of fever(40-41C0),anorexia ,emaciation, decrease of milk yield in dairy cows ,paleness of mucous membrane, lymph node enlargement and ticks were detected on different body regions .All blood and buffy coat smears of calves were positive for morula like structures inside the cytoplasm of neutrophils , lymphocytes and monocytes when staining by Giemsa and Wright stains. For all animals , the appearance of Ehrlichia spp. Organisms in leukocytes coincided with erythropenia, leukopenia, and thrombocytopenia and a decrease in hematocrit and hemoglobin concentration. For eighteen dairy cows, Ehrlichia spp. organisms were identified in leukocytes of blood and milk samples. This is apparently the first evidence for Ehrlichia spp. infection in cattle in Iraq. In conclusion, the present study documents that Ehrlichia infection exists in Mosul-Iraq and indicates that the bacterium has been present but unnoticed in the area .Further investigation will be needed in order to characterize different species of Ehrlichia infection in cattle, and explain the role of vector and imported animals in introduction of the disease to our country